INTERVENSI PENGAYAAN PENGETAHUAN PANGAN DAN GIZI PADA MUATAN LOKAL UNTUK SEKOLAH MENENGAH PERTAMA DI KABUPATEN LAMPUNG BARAT - Sungkowo Sungkowo; Budi Setiawan; Siti Madanijah (Food and Nutrition Society of Indonesia, 2008)
The problem in education especially in junior high school is low quality of education, caused by several factors such as social and economic situations. The purpose of the research was to study: 1) food and nutrition knowledge of the students; 2) food habit of the students; 3) ability to prepare traditional food of West Lampung; 4) nutritional status of students; 5) process of teaching and learning; and 6) Parent’s support. The research was conducted at junior high school in Sukau in West Lampung Regency. The research used cluster random sampling technique, one class (VIII A) was chosen as control group and another (VIII C) as treatment group. There were significant differences between control and treatment class respectively: 1) the score of food and nutrition knowledge 12.89 and 15.03; 2) the score of food habit 30.65 and 37.74; 3) the level of preparing traditional food 24.03 and 27.56; 4) the process of teaching learning 34.39 and 38.90; and 5) parent’s support 78.16 and 97.61.